Efficacy and safety of treatment with biologicals (benralizumab, dupilumab, mepolizumab, omalizumab and reslizumab) for severe eosinophilic asthma. A systematic review for the EAACI Guidelines ‐ recommendations on the use of biologicals in severe asthma. Issue 5 (24th February 2020) - Agache, Ioana; Beltran, Jessica; Akdis, Cezmi; Akdis, Mubeccel; Canelo‐Aybar, Carlos; Canonica, Giorgio Walter; Casale, Thomas; Chivato, Tomas; Corren, Jonathan; Del Giacco, Stefano; Eiwegger, Thomas; Firinu, Davide; et al.
Abstract: Five biologicals have been approved for severe eosinophilic asthma, a well‐recognized phenotype. Systematic reviews (SR) evaluated the efficacy and safety of benralizumab, dupilumab, mepolizumab, omalizumab and reslizumab (alphabetical order) compared to standard of care for severe eosinophilic asthma. PubMed, Embase and Cochrane Library were searched to identify RCTs and health economic evaluations, published in English. Critical and important asthma‐related outcomes were evaluated for each of the biologicals. The risk of bias and the certainty of the evidence were assessed using GRADE. 19 RCTs (three RCTs for benralizumab, three RCTs for dupilumab, three RCTs for mepolizumab, five RCTs for omalizumab and five RCTs for reslizumab), including subjects 12 to 75 years old (except for omalizumab including also subjects 6‐11 years old), ranging from 12 to 56 weeks were evaluated. All biologicals reduce exacerbation rates with high certainty of evidence: benralizumab incidence rate ratio (IRR) 0.53 (95% CI 0.39 to 0.72), dupilumab (IRR) 0.43 (95% CI 0.32 to 0.59), mepolizumab IRR 0.49 (95% CI 0.38 to 0.66), omalizumab (IRR) 0.56 (95% CI 0.40 to 0.77) and reslizumab (IRR) 0.46 (95% CI 0.37 to 0.58). Benralizumab, dupilumab and mepolizumab reduce the daily dose of oral corticosteroids (OCS) with high certainty of evidence. All evaluated biologicals probably improve asthma control, QoL and FEV1, without reaching the minimal important difference (moderate certainty). Benralizumab, mepolizumab and reslizumab slightly increase drug‐related adverse events (AE) and drug‐related serious AE (low to very low certainty of evidence). The incremental cost‐effectiveness ratio per quality‐adjusted life year value is above the willingness to pay threshold for all biologicals (moderate certainty). Potential savings are driven by decrease in hospitalizations, emergency and primary care visits. There is high certainty that all approved biologicals reduce the rate of severe asthma exacerbations and for benralizumab, dupilumab and mepolizumab for reducing OCS. There is moderate certainty for improving asthma control, QoL, FEV1 . More data on long‐term safety are needed together with more efficacy data in the paediatric population.